El Salvador : Technical Assistance Report-The Coordinated Direct Investment Survey and the Coordinated Portfolio Investment Survey (April 21-29, 2014). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission about the compilation of Coordinated Direct Investment Survey and Coordinated Portfolio Investment Survey (CPIS) in El Salvador. The mission recommended the authorities to research the nature of the information available that may be useful for starting the CPIS. This entails discussions regarding the forms designed during the mission for requesting information from new sources. It was also recommended to continue efforts to improve the coverage of surveys applied to nonfinancial private sector enterprises, with emphasis on the largest enterprises that are still reluctant to respond to the balance-of-payments questionnaires.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet